The Interactive Learning Revolution: A Systematic Review on Balancing Memorization and Conceptual Understanding in Mathematics - Joshua Abah Abah; Zinhle Felicia Vilakazi (International Journal of Educational Qualitative Quantitative Research, 2026)
Amid growing emphasis on the interactive learning revolution and active student engagement, this study examines the relationship between rote memorization and conceptual understanding in mathematics education. The study is theoretically grounded in David Ausubel’s Meaningful Learning Theory, which suggests that meaningful learning occurs when new knowledge is connected to learners’ existing cognitive structures. In the context of ongoing curriculum reforms and learner-centred education initiatives in South Africa, understanding this instructional relationship is crucial for shifting traditional classrooms toward interactive practices. Following the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) guidelines, a systematic literature review was conducted on empirical studies published between 2015 and 2025. A total of 36 studies were identified and synthesized using thematic analysis. The findings indicate that while memorization supports short-term recall and procedural fluency, its isolated use may limit higher-order problem-solving and active learner interaction. In contrast, conceptual approaches promote deeper understanding, mathematical reasoning, and longer-term knowledge retention. The review further suggests that a genuine instructional revolution is achieved through a balanced integration of memorization and conceptual learning, where procedural fluency supports interactive, concept-based exploration. In addition, the findings highlight the role of teacher leadership in adapting these interactive approaches to diverse and resource-constrained learning environments. These insights have implications for curriculum development, mathematics teaching practices, and teacher professional development.